THE EFFECT OF Paederia foetida L. EXTRACT ON LIVER WEIGHT OF MICE SEPSIS MODEL INFECTED WITH Escherichia coli - Savitri, Lisa; Kasimo, Elfred Rinaldo; Krissanjaya, Rochmad (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Sepsis is a critical medical condition characterized by a systemic immune response to in-fection, which can lead to severe organ dysfunction and mortality. Bacterial sepsis, par-ticularly caused by Escherichia coli, poses a significant risk due to its potential to harm tissues and organs, including the liver. The liver plays a central role in metabolic process-es and host defense during sepsis, making it a key organ of interest. This study aimed to investigate the effect of Paederia foetida leaf extract on liver weight in a mice sepsis mod-el. Mice were divided into six groups: normal control (N), negative control (K-) receiving distilled water, positive control (K+) receiving ciprofloxacin, treatment 1 (P1) receiving P. foetida extract at 100 mg/kg BW, treatment 2 (P2) receiving 300 mg/kg BW, and treat-ment 3 (P3) receiving 500 mg/kg BW. After 14 days of treatment, significant differences in liver weight were observed among the groups, with the highest mean and standard de-viation recorded in the P1 group (1.3750 ± 0.3932). Liver abnormalities, including swell-ing, lobular thickening, and weight increase, were identified, indicating the liver’s adap-tive response to toxic substances during sepsis. Interestingly, the normal control group exhibited higher liver weights compared to the treatment groups, possibly due to fatty substance accumulation within the liver tissues. These findings suggest that P. foetida ex-tract may influence liver weight changes in sepsis, potentially modulating metabolic and detoxification processes. Further studies focusing on histopathological and biochemical mechanisms are needed to clarify the therapeutic potential of P. foetida in managing liver dysfunction associated with sepsis.